The Gender Role Negotiation in the Development of Ta’aruf Relationship - Kamilah Adawiyah; Dr. Hapsari Dwiningtyas, S.Sos, MA (Interaksi Online, 2016)
Islam provides an alternative during the process of finding a life partner called as ta’aruf. Ta’aruf couple have their own uniqueness since they directly go through personal phase. As their relations developed, negotiation regarding gender role established until they enter marriage phase. The occurrence of domestic violence against woman is result of failed negotiation of gender role. Difficult depiction to understand each other in the process of ta’aruf communication would led to household problems, thus the role position between husband and wife needs to be negotiated to minimalize the so-called role disparity. This research aimed to understand the negotiation process of gender role toward the development of relation in married couple through ta’aruf process. Using phenomenology approach, this research refers to the interpretive paradigm. The research conducted using Knapp’s Relationship Model, Relational Dialectics theory, Gender Role theory, and theory of Marriage. The result of this research showed that the pattern of negotiation process through ta’aruf process could be distinguished into three, namely indirect communication using medium involving peer-group, long-distance communication accompanied by medium which background backs by power relations to perform religious justification between religious figure and parent, and direct communication using medium related with interest of parent refers to economic and religious reasons. When it enters marriage phase, conflict that usual appear due to lack of proximity emotional and trust. In the process of adapting marriage, the husband better understand the partner’s desire in the division of domestic duties which raises the role of the presence of equality by applying strategy implementing collaborative strategies style to find win win solution. However, in households ta'aruf couples who do face to face communication distance found their male dominance in limiting interaction with the outside so that can be categorized as the negotiation process unbalanced role. In contrast with the couple who perform direct communication through intermediaries, marital conflicts that arise due to the lack of wife’s trust to the husband that elicits jealousy. This can be overcome with strategies for choosing the right time to talk about the problems experienced by the wife.